Konsep Kontrak Pintar Dan Potensinya Terhadap Transaksi Pembiayaan Berasaskan Tawarruq: Smart Contract Concept and Its Potential to Tawarruq-Based Financing Transactions - Zulkepli, Muhammad Izzul Syahmi; Mohamad, Mohammad Taqiuddin; Azzuhri, Saaidal Razalli (Jurnal Fiqh, 2021)
A contract is an important concept to enable a transaction without jeopardizing the rights and security of the transaction’s parties. Its implementation varies either through traditional or modern methods. To date, the smart contract gains attention among industry players and academicians. It is a modern technological innovation that can execute a contract by utilizing a blockchain network. In particular, the researchers view that smart contracts can be adapted in products offering based on various Shariah contracts in Islamic banking institutions, such as financing products based on the tawarruq contract. Nevertheless, it requires detailed research in terms of concept and structure to measure its potential to integrate with Islamic banking operations. Therefore, this study will examine the smart contract concept as well as identify its advantages for Islamic banking institutions’ operations, particularly in tawarruqbased financing products. A qualitative approach based on library studies concerning relevant documents and literature are implemented to achieve these objectives. The collected data were then analyzed using descriptive content analysis methods. The results found that the smart contract is a contract innovation based on blockchain technology that can implement tawarruq-based financing products terms automatically, decentralized, and distributed manner. Thus, its thorough implementation can reduce the risk of faults in transactions and potentially ensure the transparency of transactions’ is well-preserved. However, further research on the risks associated with this technology, especially Shariah risks, needs to be clarified before being fully integrated into Islamic banking operations.